2020
DOI: 10.1159/000505612
|View full text |Cite
|
Sign up to set email alerts
|

Higher Postdialysis Lactic Acid Is Associated with Postdialysis Fatigue in Maintenance of Hemodialysis Patients

Abstract: Background: Postdialysis fatigue (PDF) is not an unusual symptom among hemodialysis (HD) patients; however, its causes remain unclear. The aim of this study was to analyze the factors responsible for PDF in maintenance HD patients. Methods: This was a single-center cross-sectional study conducted between March 2018 and March 2019 at the Department of Blood Purification, Beijing Chao-Yang Hospital, Capital Medical University. One hundred and fifteen HD patients were enrolled. Clinical data on demographics, como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
7
2
Order By: Relevance
“…The results of the present study are partly in disagreement with the study by Zu et al who reported that the median post-dialysis SL levels (mmol/L) were 1.6, 1.3, 1.5 in patients with no PDF, moderate PDF, and severe PDF, respectively (p = 0.013) [4]. However, if we consider the reference limits for SL reported as >2 mmoL/L, the present study demonstrates that the frequency of post-dialysis SL >2 mmoL/L does not differ significantly between patients with and without PDF similarly to the study of Zu et al Interestingly, in the study of Zu et al, studied patients were much younger than patients included in our study.…”
contrasting
confidence: 99%
“…The results of the present study are partly in disagreement with the study by Zu et al who reported that the median post-dialysis SL levels (mmol/L) were 1.6, 1.3, 1.5 in patients with no PDF, moderate PDF, and severe PDF, respectively (p = 0.013) [4]. However, if we consider the reference limits for SL reported as >2 mmoL/L, the present study demonstrates that the frequency of post-dialysis SL >2 mmoL/L does not differ significantly between patients with and without PDF similarly to the study of Zu et al Interestingly, in the study of Zu et al, studied patients were much younger than patients included in our study.…”
contrasting
confidence: 99%
“…Finally, we included 12 studies, comprising 2152 patients, in the meta-analysis (figure 1). Based on the AHRQ and NOS assessments, 11 studies8 18–27 were of moderate quality, while only 1 article28 was classified as high quality among the eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 12 eligible studies,8 18–28 published between 1996 and 2021, originating from China as well as America and Europe, are presented in online supplemental table 1. Among these studies, eight were conducted in China,18–24 28 while four took place in America and Europe 8 25–27. A single study was a prospective cohort study,28 while the remaining studies were cross-sectional8 18–27 (n=11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the fatigue of MHD patients is believed to be distinct from that of other non-hemodialysis patients and needs further exploration [ 13 ]. Previous studies have mainly focused on post-dialysis fatigue (PDF), which is the most common type of fatigue in MHD patients, and have found some new factors related to it, such as higher post-dialysis lactic acid, the number of sleep hours before HD, and peridialytic serum cytokines [ 14–16 ]. Besides PDF, fatigue symptoms can also occur before dialysis or continuously exist during a dialysis session and can be lessened or worsened by HD treatment.…”
Section: Introductionmentioning
confidence: 99%